ENHANCING WRITING SKILLS IN YOUNG LEARNERS - Raxmonova Gavxar Nuritdinovna; Baratova Munisa Rustam qizi (Western European Studies, 2024)
This study explores various effective methods to enhance the writing skills of young learners. Through a series of activities and examples, this research aims to showcase a variety of approaches that can be adopted by educators and parents to improve children’s writing abilities. The methods included in this study range from engaging storytelling sessions to interactive writing exercises, incorporating technology for digital literacy, and promoting creativity through imaginative prompts. By implementing these diverse techniques, the goal is to foster a supportive environment where young learners can develop a passion for writing while honing their skills. This study investigates the efficacy of employing a variety of methods to enhance writing skills in young learners. Traditional approaches to teaching writing often focus on standard exercises and repetitive tasks. However, this research aims to explore and implement an array of effective methods to foster the development of writing proficiency in young students. By utilizing multi-modal techniques such as creative writing exercises, visual prompts, collaborative storytelling, and digital platforms, this study seeks to engage students in diverse activities that cater to different learning styles and motivations. The research involves observation, assessment, and analysis of the impact of these varied approaches on students’ writing capabilities and overall enthusiasm for writing. The findings contribute to a deeper understanding of how multi-modal methods can effectively increase young learners’ writing skills, with implications for educational practice and curriculum development.
Keywords: Technology; Education; Teaching Methods